Relationship between ectoenzymatic activity and availability of organic substrates (Ross Sea, Antarctica): An experimental approach - Misic C.; Povero P.; Fabiano M. (Polar Biology, 1998)
Organic matter consumption and decomposition were studied in four experimental systems, having collected different organic substrates in the Ross Sea in December 1994. For the experimental approach selected, processes normally acting on a mixed pool of substances could be separated and the main features of each phenomenon could be focused on. Through the strict relationship between each experimental system and natural conditions shown by organic matter assessment, ectoenzymatic activity trends and their relation with Antarctic water substrates could be described. Through ice melting the water column becomes rich in large pools of substrates, as well as enzyme-producing micro-organisms, capable of quick development. The quantitative predominance of leucine-aminopeptidase throughout the year is well known, but its relative importance seems to decrease when, owing to production events, the environment is enriched with autotrophic- and heterotrophic-derived substances, leading to glycolytic enzymes expression. Thus, ectoenzymatic activity is supposed to be one of the factors responsible for organic matter variations, showing quantitative and qualitative changes depending on substrate availability.